Comparative evaluation of resource cycle strategies on operating and environmental impact in container terminals. (December 2015) - Lee, Byung Kwon; Low, Joyce M.W.; Kim, Kap Hwan
Highlights: Operating strategies that entail single and dual modes of resources are examined. Operating and energy efficiencies for the strategies and stowage distributions are estimated. QC collaboration with single cycling outperforms dual cycling of individual QCs. Vehicle operation supporting QC collaboration reduces the number of vehicle cycles. Cycle reductions of QCs and vehicles have little effect in reducing YC cycles. Abstract: This paper examines the use of single and dual cycle operations for three types of resources, namely, quay cranes, vehicles, and yard cranes to improve the operating efficiency and reduce the energy consumption in a container terminal. Various cycle strategies are proposed and their corresponding estimation models, describing the stowage distributions of outbound and inbound containers on a ship and the storage sharing level of blocks in the yard, are formulated to estimate the total number of cycles for the resources. Statistical analyses are conducted to evaluate and compare the effect of different cycle strategies on the cycle reductions. From the experiment results, it was found that collaboration between resources with the single cycle operation always outperforms that under the dual cycle operation without collaboration.